Formal Education and Age towards Financial Literacy: Evidence from High School Teachers - Chris Petra Agung; Teresia Debby; Mardiana Mardiana; Azzahra Kasih Dyanti; Feby Astrid Kesaulya (Soegijapranata Catholic University, 2026)
This study aimed to examine the relationship between formal education and age and the level of financial literacy among school teachers, especially in Bandung City. This study also aimed to investigate the effect of financial literacy to financial management. The study was done at JKN Senior High School (SHS) in Bandung City, with the JKN teachers as the sample. JKN SHS was chosen for several reasons, such as its alignment with the phenomenon, and the teachers in JKN SHS have diverse formal educational backgrounds and age ranges. The hypothesis testing result showed that formal education positively affects financial literacy. However, age was not shown to influence financial literacy. Thus, financial literacy positively impacts personal financial management. This outcome established an evidence-supported link to the socio-economic issue, namely the increase in urban poverty in Indonesia. In Bandung, teachers facing the demands of a consumer-driven urban life on limited income find that high financial literacy is not just advantageous but essential for developing financial resilience and preventing poverty. The observation empirically validates the claim that strong financial literacy can safeguard individuals against a decrease in their quality of life and enhance their readiness for economic emergencies and crises.